Urgensi Perlindungan Hukum Terhadap Pelaku Pengadaan Barang dan Jasa - Sepriani, Elsa (LPPM Universitas Putera Batam, 2024)
Legal protection for those involved in procuring goods and services is important because it can ensure that the process of procuring goods and services runs in accordance with applicable law. Legal protection can also prevent state losses resulting from implementation results that do not comply with specifications. The purpose of writing this article is to determine the urgency or importance of legal protection for actors procuring goods and services. This type of research is normative research. Normative research is research carried out through library research. Protection and law enforcement are the main foundations for maintaining justice and order in a country. Legal protection can provide full protection to legal subjects who are victims of violations of their rights. Procurement of government goods and services is regulated in Presidential Regulation of the Republic of Indonesia Number 16 of 2018 concerning Procurement of Government Goods/Services. In the procurement of goods or services, problems often occur. Therefore, legal protection for actors procuring goods or services is absolutely necessary